Pengaruh Kualitas Kehidupan Kerja Terhadap Kinerja Karyawan PT.Polowijo Gosari - FUJI ASTUTIK, MERI (Jurnal Ilmu Manajemen (JIM), 2018)
This research aims to know and test the influence quality of work life (safe and healthy work environment, the development of human capabilities, and the growth and scurity) on performance of employees of PT. Polowijo Gosari. The approach used in this research is quantitative, where is the population used in this research was 207 people using teknik proportionate startified random sampling techniques which amounted to 136 employees. data analysis technique used was multiple linear regression with the help of the software SPSS version 17. Simultaneously, research results obtained the results that the safe and healthy work environment, the development of human capabilities, and the growth and scurity simultaneously affects the performance of the employee. the magnitude of the influence caused by both the independent variable was 80.6%, and 19.1% the influence by other outside variables of the study. Then partially variable quality work life (safe and healthy work environment to have a positif influence on performance employees, the development of human capabilities to have a positif influence on performance employees, and the growth and scurity to have a positif influence on performance employees). Keywords: quality of work life and performance